3 oranges / 4 friends = 3/4 orange for each of them, or 0.75 orange each
(You can check the answer by saying, if each of them get 3/4 of an orange, then multiplying that by the 4 friends should give me the 3 oranges. 3/4 x 4 = 3, so it's correct).
Answer:
IM ON THE SAME ONEEE let me know when you have it
Step-by-step explanation:
Answer:
(- 4, - 10 )
Step-by-step explanation:
Given the 2 equations
y = x - 6 → (1)
x = - 4 → (2)
Substitute x = - 4 into (1) for corresponding value of y
y = - 4 - 6 = - 10
Solution is (- 4, - 10 )
Answer:
A
Step-by-step explanation: